Personality and online news commenting behaviours: uncovering the characteristics of those below the line. Issue 1 (November 2018) - Barnes, Renee; Mahar, Doug; Cockshaw, Wendell; Wong, Ides
Commenting on the news is one of the most common forms of participation in news use and one of the most prevalent forms of citizen engagement online. However, very little research has focused on the characteristics of those who contribute to news websites and how this influences their commenting behaviour. Drawing on the Big Five Inventory of personality traits, this exploratory study examines how personality impacts upon the frequency of commenting and motivations for commenting on news websites. Overall, we find that less agreeable and more open to new experiences individuals commented more. Those individuals who demonstrate high levels of neuroticism were more likely to comment on stories which impacted them emotionally. Those who were disagreeable were more likely to comment on a story when they disagreed with the journalist. Those with lower levels of conscientiousness were more likely to comment if they disagreed with other commenters. Finally, disorganised and disagreeable individuals were more likely to comment to see the reaction of other commenters.